Insulin-like growth factor II mediates epidermal growth factor-induced mitogenesis in cervical cancer cells. - Steller, M A (1995)
There is increasing evidence that activation of the insulin-like growth factor I (IGF-I) receptor plays a major role in the control of cellular proliferation of many cell types. We studied the mitogenic effects of IGF-I, IGF-II, and epidermal growth factor (EGF) on growth-arrested HT-3 cells, a human cervical cancer cell line. All three growth factors promoted dose-dependent increases in cell proliferation. In untransformed cells, EGF usually requires stimulation by a "progression" factor such as IGF-I, IGF-II, or insulin (in supraphysiologic concentrations) in order to exert a mitogenic effect. Accordingly, we investigated whether an autocrine pathway involving IGF-I or IGF-II participated in the EGF-induced mitogenesis of HT-3 cells. With the RNase protection assay, IGF-I mRNA was not detected. However, IGF-II mRNA increased in a time-dependent manner following EGF stimulation. The EGF-induced mitogenesis was abrogated in a dose-dependent manner by IGF-binding protein 5 (IGFBP-5), which binds to IGF-II and neutralizes it. An antisense oligonucleotide to IGF-II also inhibited the proliferative response to EGF. In addition, prolonged, but not short-term, stimulation with EGF resulted in autophosphorylation of the IGF-I receptor, and coincubations with both EGF and IGFBP-5 attenuated this effect. These data demonstrate that autocrine secretion of IGF-II in HT-3 cervical cancer cells can participate in EGF-induced mitogenesis and suggest that autocrine signals involving the IGF-I receptor occur "downstream" of competence growth factor receptors such as the EGF receptor.